Communication Experience and Self-Concept of Female Online Taxi Drivers in Bogor City - Salsabilla, Syifa Zahra; Utamidewi, Wahyu; Budhiharti, Tri Widya (Al Huwiyah: Journal of Woman and Children Studies, 2024)
Nowadays, women are often constructed by society as individuals who are calm, gentle, thorough, and are in the domestic realm, such as the household, caring for children. However, there are women who choose to become online taxi drivers as their job, and the existing social construction that this profession is a masculine profession does not discourage female online taxi drivers from continuing to earn a living. The aim of this research is to find out how female online taxi drivers interpret their goals in carrying out their profession and their motives in carrying out their profession, as well as their communication experiences as online taxi drivers. The research results show that the average motive behind women in the city of Bogor choosing to work as online taxi drivers is economic factors, such as being a single parent or simply helping their husband with their family's economy to earn income from their work as an online taxi driver.